Intersections between basic and higher education in the construction of a curricular policy: the teaching dimension for/in the achievement of the proposal - Soares, Marcia Torres Neri; Soto, Ana Paula de Oliveira Moraes; Oliveira, Simone Dias Cerqueira de (Debates em Educação, 2026)
This text aims to discuss the construction of the Curricular Proposal (CP) of the Municipal Public Network of Feira de Santana-BA against the background of one of the dimensions that can be problematized in the light of the articulation between Basic and Higher Education: the teaching dimension and subsequent initiatives within the local context. Thus, qualitative study is based on the methodological movement of action research and, on the scale intended in this article, considers the collaboration of beginning teachers and their dialogues with teachers/researchers from higher education institutions to/in elaborating a curricular policy. Furthermore, we consider the repercussions a) of academic training and b) for the academic training of the collaborators participating in the CP, expressed both from the point of view of teachers with stricto sensu training at the time of the composition of the CP elaboration group - of academic training; and of postgraduate teachers, also at a stricto sensu level, during and/or after their participation in the group – for academic training. To some degree, the writing effort also marks the methodological movement developed with the teachers of the referred Network through Training in School Curriculum (FormaCE). The study’s results confirm/reveal: I. the relevance of the dialogues between the two levels of Brazilian education; II. the intersections with discussions about teacher education, especially of beginning teachers and investments in their academic trajectories; III. the importance of research already carried out based on the experiences arising from the construction of CP; IV. the possibilities from the point of view of new scientific productions and; V. contributions to/in the elaboration of other curricular policies. The possibilities of teacher participation in elaborating a curricular proposal are challenging and fruitful, and numerous can be the analysis and methodological aspects of (re)creation in different spaces.